Hormesis-induced gap between the guidelines and reality in ecological risk assessment. (March 2020) - Zhang, Xiaoxian; Lin, Zhifen
Abstract: Guidelines of ecological risk assessment (ERA) used worldwide, based on S-shaped threshold dose-response curve, fail to consider hormesis, a biphasic dose-response model represented as a J-shaped or an inverted U-shaped curve, that occurs in real-life environment. Now that humans are routinely exposed to chemicals below the threshold where hormetic stimulation prevails, it is noteworthy that over-strictness about chemical control also means a waste of limited resources. So hormesis leads to the gap between guidelines with S-shaped model and reality with hormesis model concerning ERA. In this study, hormetic effects of sulfachloropyridazine (SCP) on the bioluminescence of Aliivibrio fischeri ( A. f ) under 41 conditions to simulate the real environment were investigated and compared with ERA practice by some parameters, such as no observed effect concentration (NOEC), hormetic-stimulatory range (HSR) and goal concentration (GC). Not only is the reproducibility of hormesis in real-life contexts confirmed, binomial distribution (p = 0.644 > 0.05) of the relative position of GC and HSR is also found, revealing a 50% probability for GC to falls in HSR, which proves the over-strictness of ERA both qualitatively and quantitatively. This study provides a novel view for ERA that hormetic principles should dominate, and conditions where S-shaped dose-response model works should be singled out on a specific basis to bridge the hormesis-induced gap. Graphical abstract: Image 1 Highlights: Hormesis reflects biological effects on A. fischeri in reality. Two types of relative position of GC and HSR are binomially distributed. The unreliability of current ecological risk assessment parameters is revealed. Chemicals showing S-shaped responses should be treated case-by-case. Hormesis-induced gap can be bridged by hormesis model with probability method.